2021
DOI: 10.54393/pbmj.v4i2.170
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety culture: a survey of private sector tertiary care hospital of Lahore, Pakistan

Abstract: Patient safety is a critical component to improving healthcare quality. Due to the potential of growing recognition and importance of establishing a patient safety culture within healthcare organizations, assessing existing patient safety culture is a prerequisite. Despite a vital role in delivering quality care, little attention has been given to describe healthcare professionals' perceptions and expectations of the patient safety culture in Pakistan. Objective:The current study aimed to assess the patient sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Hastings, R. P., & Oakford, S. (2003) reported positive opinion and perceptions of parents and teachers for the inclusion of special need children and ESBD. Many studies in Pakistan on inclusion of special need children concluded that teachers of mainstream educational institutions including universities are reluctant (Hameed, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hastings, R. P., & Oakford, S. (2003) reported positive opinion and perceptions of parents and teachers for the inclusion of special need children and ESBD. Many studies in Pakistan on inclusion of special need children concluded that teachers of mainstream educational institutions including universities are reluctant (Hameed, 2014).…”
Section: Introductionmentioning
confidence: 99%